2011
DOI: 10.1016/j.ejcts.2010.07.039
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorodeoxyglucose positron emission tomography-computerized tomography and lung cancer: a significant referral bias exists

Abstract: The estimate of the accuracy of PET-CT scan is significantly influenced by referral bias, and a strong reliance is placed on its results. Furthermore, patients with a positive PET-CT scan are more likely to undergo tissue sampling as the SUV increases. Given the relatively low sensitivity of the PET-CT scan in detecting disease and its poor performance in the mediastinum, the PET-CT scan may have too high an impact on the decision to undergo further invasive diagnostic procedures. Patients should not be deferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…14,24,26-29,32,39,45,46,48,50,52-54,58,60,62,64,67-69,72,74,75,77,80-83,85-88 In comparison, 23 studies with an average or median diameter greater than 2 cm had a slightly higher average adjusted sensitivity (91% [95% CI, 89%-93%]). 10,11,15,25,30,31,34,35,37,41,43,44,55-57,61,63,73,76,78,79,84,86 Specificity of FDG-PET to diagnose lung cancer was not significantly influenced by lesion size (74% for studies with lesions ≤2 cm and 75% for studies with larger average lesion size).…”
Section: Resultsmentioning
confidence: 94%
“…14,24,26-29,32,39,45,46,48,50,52-54,58,60,62,64,67-69,72,74,75,77,80-83,85-88 In comparison, 23 studies with an average or median diameter greater than 2 cm had a slightly higher average adjusted sensitivity (91% [95% CI, 89%-93%]). 10,11,15,25,30,31,34,35,37,41,43,44,55-57,61,63,73,76,78,79,84,86 Specificity of FDG-PET to diagnose lung cancer was not significantly influenced by lesion size (74% for studies with lesions ≤2 cm and 75% for studies with larger average lesion size).…”
Section: Resultsmentioning
confidence: 94%
“…1). The characteristics of the 56 studies was shown in Supporting Information Table 1 4–6, 14, 23–74. Among the included studies, 46 evaluated LN metastatic disease and 13 assessed extrathoracic metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
“…Data are pooled estimates for all 24 studies(9,11,12,17,21,23,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(47)(48)(49)51,52…”
mentioning
confidence: 99%